Variations of snow accumulation rate in Central Antarctica over the last 250 years - A. Ekaykin A.; D. Vladimirova O.; V. Lipenkov Ya.; А. Екайкин А.; Д. Владимирова О.; В. Липенков Я. (Ice and Snow, 2017)
The present-day global climate changes, very likely caused by anthropogenic activity, may potentially present a serious threat to the whole human civilization in a near future. In order to develop a plan of measures aimed at elimination of these threats and adaptation to these undesirable changes, one should deeply understand the mechanism of past and present (and thus, future) climatic changes of our planet. In this study we compare the present-day data of instrumental observations of the air temperature and snow accumulation rate performed in Central Antarctica (the Vostok station) with the reconstructed paleogeographic data on a variability of these parameters in the past. First of all, the Vostok station is shown to be differing from other East Antarctic stations due to relatively higher rate of warming (1.6 °C per 100 years) since 1958. At the same time, according to paleogeographic data, from the late eighteenth century to early twenty-first one the total warming amounted to about 1 °C, which is consistent with data from other Antarctic regions. So, we can make a conclusion with high probability that the 30-year period of 1985–2015 was the warmest over the last 2.5 centuries. As for the snow accumulation rate, the paleogeographic data on this contain a certain part of noise that does not allow reliable concluding. However, we found a statistically significant relationship between the rate of snow accumulation and air temperature. This means that with further rise of temperature in Central Antarctica, the rate of solid precipitation accumulation will increase there, thus partially compensating increasing of the sea level. Современные изменения температуры воздуха и скорости накопления снега, полученные инструментальным путём на антарктической станции Восток, сопоставлены с палеоклиматическими реконструкциями за последние 250 лет. Показано, что период 1985–2015 гг., вероятно, был самым тёплым 30-летием за последние 2,5 века. Скорость снегонакопления положительно коррелирует с изменчивостью температуры ...